Ernährung und Demenz – Demenz und Ernährung - Volkert, Dorothee (Therapeutische Umschau. Revue therapeutique, 2023)
Nutritional aspects play an important role both in the prevention of dementia and in its course. There is a mutual relationship between cognitive impairment and nutrition. In terms of prevention, nutrition is one of the potentially modifiable risk factors for the development of the disease, since it can influence both the structures and the functionality of the brain in a variety of ways. A food selection based on the traditional Mediterranean diet or on a generally healthy diet also seems to be advantageous for maintaining cognitive function. In the course of dementia, various symptoms of the disease sooner or later lead to nutritional problems, which make it difficult to achieve a varied, needs-based diet and are associated with an increased risk of a qualitatively and quantitatively inadequate nutrition. In order to maintain a good nutritional status in people with dementia for as long as possible, early detection of nutritional problems is fundamental. Strategies for the prevention and treatment include the elimination of potential causes of malnutrition and various supportive measures to promote adequate eating. The diet itself can be supported by an attractive, varied range of food, additional snacks, enrichment of the food with energy and nutrients and by oral nutritional supplements. Enteral or parenteral administration of nutrients, on the other hand, should be reserved for justified exceptional cases.
CRIS-Team Scopus Importer:2023-06-09